UMPSA seals partnership with BEIBU Gulf University - Mimi Rabita, Abd Wahit (UMPSA, 2024)
QINZHOU CITY, CHINA, 4 June 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) collaborates with BEIBU Gulf University (BGU) located in Qinzhou City, China, to focus on academic collaboration, staff and student exchange, research development, and edutourism programmes that benefit both universities.